2007
DOI: 10.1111/j.1471-4159.2007.04853.x
|View full text |Cite
|
Sign up to set email alerts
|

Cyclic AMP‐dependent protein kinase (PKA) phosphorylates Ser362 and 467 and protein kinase C phosphorylates Ser550 within the M3/M4 cytoplasmic domain of human nicotinic receptor α4 subunits

Abstract: Studies have suggested that the expression, translocation, and function of a4b2 nicotinic receptors may be modulated by a4 subunit phosphorylation, but little direct evidence exists to support this idea. The objective of these experiments was to identify specific serine/threonine residues on a4 subunits that are phosphorylated in vivo by cAMP-dependent protein kinase and protein kinase C (PKC). To accomplish this, DNAs coding for human a4 subunits containing alanines in place of serines/threonines predicted to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
40
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(43 citation statements)
references
References 35 publications
3
40
0
Order By: Relevance
“…None of the a4 variants examined in this study are predicted to affect any of these 17 sites; however, there was a significant discrepancy in the phosphorylation patterns of the identifiable serine residues across the four a4 variants. Consistent with previous studies (Pollock et al, 2007), we observed phosphorylation of serine residues only on the M3-M4 loop of the a4 subunit (Table 6). Proteolysis of the ha4 subunit by trypsin and LysC prior to LC-MS/MS restricts the absolute coverage of the receptor by producing peptide fragments too small to be unambiguously assigned, and so we anticipated missing 8 of 17 possible phosphorylation sites.…”
Section: Effects Of Ha4 Variants On Associated Proteins and Phosphorysupporting
confidence: 81%
See 1 more Smart Citation
“…None of the a4 variants examined in this study are predicted to affect any of these 17 sites; however, there was a significant discrepancy in the phosphorylation patterns of the identifiable serine residues across the four a4 variants. Consistent with previous studies (Pollock et al, 2007), we observed phosphorylation of serine residues only on the M3-M4 loop of the a4 subunit (Table 6). Proteolysis of the ha4 subunit by trypsin and LysC prior to LC-MS/MS restricts the absolute coverage of the receptor by producing peptide fragments too small to be unambiguously assigned, and so we anticipated missing 8 of 17 possible phosphorylation sites.…”
Section: Effects Of Ha4 Variants On Associated Proteins and Phosphorysupporting
confidence: 81%
“…The effects of the rare CHRNA4 variants on nAChR binding site production, plasma membrane trafficking, and upregulation by nicotine are further supported by proteomic studies. The a4 subunit of the nAChR is phosphorylated on several sites within the M3-M4 loop (Wecker et al, 2001;Pacheco et al, 2003;Pollock et al, 2007Pollock et al, , 2009), and we augmented the proteomic study by enriching for phosphopeptides prior to LC-MS/MS to identify and profile potential shifts in the phosphorylation state of nAChR subunits and other putatively associated proteins attributable to the presence of the a4 rare variants. The degree of difference relative to the common variant may identify interesting targets for future mechanistic studies and is an indicator of the severity of effect of a single amino acid substitution on the function/assembly/trafficking of a4b2 nAChRs conferred by these rare a4 variants.…”
Section: Discussionmentioning
confidence: 99%
“…This cytoplasmic loop is also important for interaction with intercellular proteins, which could increase the stability of α4β2 nAChRs (41), as well as post-translational modification of the α4 subunit (42). Our imaging study showed that for nonsmokers, specific rare variants in the CHRNA5 gene region encoding the cytoplasmic loop could increase the availability of α4β2 nAChRs in multiple brain regions.…”
Section: Discussionmentioning
confidence: 99%
“…KOs and found no staining when compared to the wild type mice, (2) Pollock et al (2007) who used two b2 antibodies (MAb270 and sc-11372) and found that both gave similar results in immunoblots of brain cells, and (3) Kabbani and Levenson (2007) who performed a similar proteomic study to Paulo et al (2009) and found no b2 band in the Western blot or the corresponding coomassie stained gel within the KO homogenised brain tissue compared to the wild type tissue.…”
Section: Immunohistochemistrymentioning
confidence: 92%